2014
DOI: 10.1002/2013jc009780
|View full text |Cite
|
Sign up to set email alerts
|

Ocean response to volcanic eruptions inCoupledModelIntercomparisonProject 5 simulations

Abstract: We examine the oceanic impact of large tropical volcanic eruptions as they appear in ensembles of historical simulations from eight Coupled Model Intercomparison Project Phase 5 models. These models show a response that includes lowering of global average sea surface temperature by 0.1-0.3 K, comparable to the observations. They show enhancement of Arctic ice cover in the years following major volcanic eruptions, with long-lived temperature anomalies extending to the middepth and deep ocean on decadal to cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
107
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 61 publications
13
107
0
Order By: Relevance
“…It appears that the results from the CMIP5 project are largely consistent with Stenchikov et al [59,60]. Ding et al [116] The northern hemisphere anomalies of maximum and minimum ice mass (10 15 kg) for the Pinatubo ensemble.…”
Section: P0230supporting
confidence: 80%
See 2 more Smart Citations
“…It appears that the results from the CMIP5 project are largely consistent with Stenchikov et al [59,60]. Ding et al [116] The northern hemisphere anomalies of maximum and minimum ice mass (10 15 kg) for the Pinatubo ensemble.…”
Section: P0230supporting
confidence: 80%
“…Ding et al [116] found that all models consistently show an annual average reduction of the surface incoming solar radiation by 1 W m À2 -5 W m À2 . The global sea surface temperature decreases by 0.1 K-0.3 K. The cool SST signal penetrates in the deep ocean, decreasing temperature in the upper 1000-m layer by roughly 0.03 K. Sea ice extent and mass grow by 5%.…”
Section: P0260mentioning
confidence: 96%
See 1 more Smart Citation
“…Liu et al 2016). Sea ice in the Northern hemisphere is also affected by large volcanic eruptions and SVEs can cause up to a decade of increased Arctic sea ice extent (Ding et al, 2014;Gagné et al, 2017). Gagné et al (2017) for example demonstrated that the sea ice response to SVEs is dependent on pre-eruption temperature conditions with warmer preeruption climate leading to a stronger sea ice response.…”
Section: Introductionmentioning
confidence: 99%
“…The negative radiative forcing induces several responses in the Earth system (Timmreck 2012;Zanchettin 2017), including expansion of sea-ice (Miller et al 2012), changes in atmospheric (Robock and Mao, 1992) and ocean circulation (Ding et al 2014), and perturbations to modes of variability (Lehner et al 2016;Maher et al 2015). These responses are partly dependent on the climate state prior to an eruption, as well as the location of the volcano and the season of Abstract Volcanic eruptions are an important influence on decadal to centennial climate variability.…”
Section: Introductionmentioning
confidence: 99%